Corporate Governance and Forensic Accountant: an Exploratory Study - Madan Lal Bhasin (Journal of Accounting, Business and Management (JABM), 2013)
An increasing number of researchers are finding that poor corporate governance (CG) is a leading factor in poor performance, manipulated financial reports, and unhappy stakeholders. The recent accounting scandals (Enron, WorldCom, Madoff, Satyam, etc.) have induced a crisis of confidence in financial reporting practice and effectiveness of CG mechanisms. Corporations and regulatory bodies are, therefore, trying to analyze and correct any existing defects in their reporting system. In the current reporting environment, forensic accountants (FA's) are in great demand for their niche accounting, auditing, legal, and investigative skills. Influenced by business, government, regulatory authorities and the courts, there is evidence that a higher level of expertise is now required to analyze present-day complicated financial transactions and events. As a result, forensic accounting has been thrown in the forefront of the crusade against financial deception and accounting scandals. This paper investigates through a survey study, which was conducted in the National Capital Region of India during 2011-12, if there are differences in the views of the relevant skills of FA's among accounting practitioners, academics, and users of forensic accounting services. In all, nine questions were asked to 40 practitioners, 80 academics and 80 users of forensic accounting services that pertain to solicit their views of what skills are deemed inherently important to FA's? At present, some Universities in India are considering adding forensic accounting course to their curriculum. The results of the present study may provide some guidance to educators for the development of forensic accounting curriculum by identifying the pertinent skills to accompany a program of study.